FRI0202 Late onset neutropaenia in patients with rheumatoid arthritis after rituximab treatment. (23rd January 2014) - Abdulkader, R.; Dharmapalaiah, C.; Shand, L.; Rose, G.; Clunie, G.; Watts, R.
Abstract : Background: Late onset neutropaenia (LON) is a recognised complication of rituximab (RTX) treatment in patients with haematological malignancies. There is increasing evidence that LON can also complicate B-cell depletion in patients with rheumatological conditions including rheumatoid arthritis (RA). 1 Objectives: To identify the frequency of LON occurring after RTX therapy in rheumatoid arthritis patients. Methods: Retrospective review of patients with RA treated with RTX between October 2007 and July 2011. Patients were identified from the day unit records, case notes and haematology results were reviewed. LON was defined as absolute neutrophil count <1.5×10 9 /l occurring at least 4 weeks after RTX.For each patient we recorded demographics, serology, concurrent DMARDs, number of cycles of RTX, neutrophil count pre treatment and up to one year after the last cycle. RTX regime was 1g IV given 2 weeks apart. Repeated as clinically needed but not less than 6 monthly. FBC was monitored according to DMARD guidelines or 3 monthly, or at the time of clinical review. Results: Over this period 108 patients with RA were treated with RTX (72% women). Median age 64 years (25-86). 96 patients were sero-positive for RF or ACPA (9 negative, 3 unrecorded). 66.6% were on a concurrent DMARD. The total number of RTX cycles received was 237. Patients received up to 8 cycles of RTX, median 2. 5 patients (4.6%) developed LON after a mean of 142 days. 3 were were taking DMARDS.Doses were stable prior to starting RTX. 2 were not on DMARDS. LON occurred after 2.1% of all cycles. LON was complicated by neutropaenic sepsis with pneumonia in 2 patients. 2 patients were treated with Granulocyte colony stimulating factor (G-CSF):1 chest infection, 1 recent joint replacement. Neutropaenia was transient with a maximum duration of 15 days.LON did not recur in 2 patients who were retreated with RTX (follow up >6 months). Conclusions: In our patients, RTX treatment was complicated by LON in 4.6%, this compares to 3% incidence reported by Tesfa et al. 1 LON followed 2.1% of treatment cycles and was associated with infections in 40% of the patients. We may have underestimated the frequency of LON as we did not routinely check FBC after RTX except in patients on DMARDs.LON may occur after only one treatment cycle of rituximab, several months after therapy and can be profound.It is therefore imperative that we are aware of LON and monitor FBC; the frequency of monitoring is uncertain as LON is transient. References: Tesfa D, Ajeganova S, Hägglund H, Sander B, Fadeel B, Hafström I, Palmblad J. Late-onset neutropenia following rituximab therapy in rheumatic diseases: association with B lymphocyte depletion and infections. Arthritis Rheum. 2011 Aug;63(8):2209-14 Disclosure of Interest: R. Abdulkader: None Declared, C. Dharmapalaiah: None Declared, L. Shand: None Declared, G. Rose: None Declared, G. Clunie: None Declared, R. Watts Consultant for: Received consultancy fees from Roche